Case report: Adult NTRK-rearranged spindle cell neoplasms with TPM3-NTRK1 fusion in the pelvic - Cao, Qiurui; Huang, Zhifang; Liang, Hong; Hu, Xing; Wang, Lucas; Yang, Yaxian; Lian, Bin; Huang, Jian; Guo, Jinyan (Frontiers in Oncology, 2024)
NTRK-rearranged spindle cell neoplasms (NTRK-RSCNs) are rare soft tissue tumor molecularly characterized by NTRK gene rearrangement, which occurs mostly in children and young adults, and rarely in adults. The abnormal tumor located in superficial or deep soft tissues of human extremities and trunk mostly, and rarely also involves abdominal organs. In this case, we report a malignant NTRK-RSCN that occurred in the pelvic region of an adult. The patient was found to have a large tumor in the pelvic region with a pathological diagnosis of infiltrative growth of short spindle-shaped tumor cells with marked heterogeneity. Immunohistochemistry of this patient showed positive vimentin, pan-TRK and Ki67 (approximately 60%) indicators with negative S100, Desmin and DOG1. Molecular diagnosis revealed c-KIT and PDGFRα wild type with TPM3-NTRK1 fusion, unfortunately this patient had a rapidly progressive disease and passed away. This case highlights the gene mutation in the molecular characteristics of NTRK-RSCNs, and the significance of accurate molecular typing for the diagnosis of difficult cases.